El Contexto Histórico y Geográfico de los monolitos de la colina Lluishi de la parroquia el Rosario y el desarrollo socio cultural del cantón Guano, provincia de Chimborazo. - León Paguay, Sandra Fernanda (2017)
The Lluishi Hill a variety of monoliths or figures carved in stone both old and modern, among the most outstanding are the face of the Inca, the vessel and the face of fish referring to tve ancient figures, and those figures elaborated nowadays have been designed by handicraftsmen belonging to the Association of stonecutters “21 de Abril” belonging to the San Pablo neighborhood, San Andrés parish, the contemporary figure represents the Chimborazo snow-capped mountain, the carpet making, the hard work of the people are embodied in pictographs on each one of monoliths, as part of artistic skill the sculptures contribute to the economic, historical, cultural and tourist development of the Guano county. There are natural monoliths that have been constructed by the nature and elaborated by the man they are in the habit of being monuments of ceremonial or artistic type that realice from one only block of stone. The general objetive of the research is to analyze how the historical, social and geographical context of the monoliths of the Lluishi hill from Rosario parish contribute to the socio-cultural development of the Guano county. The research work, methodologically approaches the perspective of a quasi-experimental design, is qualitative and to dealing of a descriptive research is eminently social, the technique applied to the data gathering was the interview, in which, the interpretation procedures were executed and thus to find the results that allowed to reach the respective conclusions.